Impact of the context of socioscientific issues on discourse patterns used in science classes - İREZ, OSMAN SERHAT; HAN TOSUNOĞLU, ÇİĞDEM (My University, 2023)
This study is a qualitative study conducted to examine the effect of socioscientific issues (SSI) on discourse patterns used in the classroom. The research was conducted with four elementary science teachers working in a public school. The research was designed as case studies of these four teachers and data resources were video recordings of these teachers’ routine and SSI based lessons. The data was analyzed through discourse analysis. The discourse patterns used by teachers were examined in terms of adjacent the utterance, triadic, and chain discourse patterns. The results indicated that the discourse patterns used by the teachers in their routine lessons changed dramatically in the context of SSI and the chain discourse pattern came to the fore in the courses processed in the context of the SSI.
Keywords: Case study; Discourse Patterns; Science Education; Socioscientific Issues